1996
DOI: 10.1042/bj3190117
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in utilization of N-glycosylation sites Asn624 and Asn138 in human lactoferrin: a study with glycosylation-site mutants

Abstract: Human lactoferrin (hLF) is a glycoprotein involved in the host defence against infection and excessive inflammation. Our objective was to determine to what extent each of the three sequons for N-linked glycosylation in hLF is actually used. Human kidney-derived 293(S) cell lines expressing recombinant hLF (rhLF) or glycosylation-site mutants were produced. The mutations involved replacement of asparagine residues with glutamine at one or more sequons for N-glycosylation (Asn138, Asn479 and Asn624). Comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 38 publications
4
61
0
Order By: Relevance
“…Human lactoferrin (hLF) is a glycoprotein that has mostly core-fucosylated glycans at the two N-glycosylation sites (48,49); this was confirmed by MS analysis (Fig. 5A and supplemental Table S2).…”
Section: Endo-m Variant Acting On Core-fucosylated N-glycansmentioning
confidence: 58%
“…Human lactoferrin (hLF) is a glycoprotein that has mostly core-fucosylated glycans at the two N-glycosylation sites (48,49); this was confirmed by MS analysis (Fig. 5A and supplemental Table S2).…”
Section: Endo-m Variant Acting On Core-fucosylated N-glycansmentioning
confidence: 58%
“…It has been demonstrated that Asn138 and Asn479 are preferentially Nglycosylated in LF produced in human kidney-derived 293(S) cell lines, indicating site-specific heterogeneity [35]. However, all three N-linked sites of rhLF from our glycoengineered P. pastoris are predominantly occupied as characterized by peptide mapping and LC-MS (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Glycosylation at a single site (N479) or at all three sites (N138, N479, and N624) occurs in only approximately 5% and 9% of hLF, respectively [35]. In order to determine Nglycosylation occupancy of each site, rhLF was digested with trypsin.…”
Section: Generation Of Sialylated Bi-antennary Rhlf By In Vitro Sialymentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative recombinant human and natural bovine lactoferrin analyses were conducted by enzyme-linked immunosorbent assays (ELISAs). hLf was measured by an rhLf-specific ELISA according to the procedure recommended by Pharmingen, and anti-hLf was adsorbed with Sepharose to remove cross-reacting antibodies (54). bLf levels were measured using a bovine lactoferrin ELISA quantitation kit (Bethyl Laboratories, Inc.).…”
Section: Methodsmentioning
confidence: 99%